2022
DOI: 10.1016/j.esmoop.2021.100356
|View full text |Cite
|
Sign up to set email alerts
|

Results of a single-arm pilot study of 32P microparticles in unresectable locally advanced pancreatic adenocarcinoma with gemcitabine/nab-paclitaxel or FOLFIRINOX chemotherapy

Abstract: Background Unresectable locally advanced pancreatic cancer (LAPC) is generally managed with chemotherapy or chemoradiotherapy, but prognosis is poor with a median survival of ∼13 months (or up to 19 months in some studies). We assessed a novel brachytherapy device, using phosphorous-32 ( 32 P) microparticles, combined with standard-of-care chemotherapy. Patients and methods In this international, multicentre, single-arm, open-label pilot study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…32 P was only injected percutaneously with CT guidance and achieved a tumour dose between 1255 and 19 000 Gy 58 , 59 , 61 . This dose was a notably higher dose than the dose of 100 Gy achieved by the more recent microparticle brachy­therapy utilizing EUS application 24 , 60 .…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…32 P was only injected percutaneously with CT guidance and achieved a tumour dose between 1255 and 19 000 Gy 58 , 59 , 61 . This dose was a notably higher dose than the dose of 100 Gy achieved by the more recent microparticle brachy­therapy utilizing EUS application 24 , 60 .…”
Section: Resultsmentioning
confidence: 78%
“…The authors also found the highest complication rate, with 75 greater than or equal to grade III complications in 16 of 18 patients (89 per cent) 58 , followed closely by Ross et al . 24 (2021) with 139 greater than or equal to grade III complications in 34 of 42 patients (81 per cent). In contrast, Ross et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations